IMPLEMENTASI PERATURAN KODE ETIK TERHADAP ANGGOTA POLRI YANG MELANGGAR KETENTUAN PIDANA - Abdul Kalam Azad; Arifai; Abdul Jabal Rahim (Halu Oleo University, 2024)
This study aims to determine the implementation of the code of ethics regulations against members of the Indonesian National Police who violate criminal provisions. This research method combines normative and empirical approaches to analyze the implementation of the code of ethics regulations against members of the Indonesian National Police who violate criminal provisions. The method of processing and analyzing data uses data listing, data coding, tabulation, and data analysis. The results of the study indicate that the enforcement of the code of ethics for members of the Indonesian National Police is very important to improve the professionalism and positive image of the police. Factors that influence the enforcement of this code of ethics can be categorized into external and internal factors, as well as cultural factors that influence the culture of the police organization. By considering these factors and implementing the right strategy, it is hoped that the enforcement of the code of ethics for members of the Indonesian National Police can improve professionalism, improve the image of the Indonesian National Police, and increase public trust in the police institution.